Mandatory Adoption of International Financial Reporting Standards (IFRS) in Nigeria: The Unresolved Institutional Question - Isenmila, P.A.; Adeyemo, Kingsley Aderemi (Richtmann Publishing, 2013)
Preeminently, the objective of the paper is to examine the perceived impact of Nigerian institutional infrastructure (i.e.Educational Institution, Professional Accounting Bodies, Legal Framework, SEC and NASB or FRCN) on the mandatoryadoption of IFRS, which took effect from January 2012. The study adopts the questionnaire survey method to seekrespondents’ views on the subject matter. One of the major perceived differences between IFRS and Nigerian SAS is that theformer allegedly provides more discretion (i.e., less specific standards and less implementation guidance). Although morereporting discreetness is not necessarily a challenge, firms’ reporting incentives, which are shaped by Nigerian institutionalframework, play a foremost role in how organizations would apply the discernment under IFRS. We therefore employedMultiple Regression techniques as well as One Way Repeated Measure Analysis of Variance, in testing the two hypotheses inthe paper. The result shows that four of the five institutions are ready and strong enough to support the mandatory adoption ofIFRS.We recommended interalier, that the capacity of regulators (Corporate Affairs Commission,Securities and ExchangeCommission, National Insurance Commission, Central Bank of Nigeria to mention but a few) must be strengthened so as toenable them to effectively deal with accounting and financial reporting practices of the regulated concerns, so that themandatory adoption of IFRS in Nigeria, does not become a mere labeled or nominal one.